Long lasting effects of the conversion from natural forest to poplar plantation on soil microbial communities - Vitali, Francesco; Mastromei, Giorgio; Senatore, Giuliana; Caroppo, Cesarea; Casalone, Enrico (Microbiological research, 2016)
[Display omitted] In this study, we evaluate the long-lasting effects on soil microbial communities of a change within a single land-use category, specifically the conversion from natural forest to forest plantation. To minimize the effects of impacts other than land-use (i.e., climatic and anthropogenic), we chose three sites within a Natural Park, with homogeneous orographic and soil texture characteristics. We compared microbial diversity in a total of 156 soil samples from two natural mixed forests and a similar forest converted to poplar plantation about thirty years ago. The diversity and structure of bacterial and fungal communities were investigated by terminal restriction fragments length polymorphism (T-RFLP) analysis of the 16S-rRNA gene and the ITS-rDNA regions, respectively. Bacterial and fungal communities from the forest plantation, compared to those from natural forest soils, showed different community structure and lower α-diversity values, consistently with the significantly higher pH values and lower organic matter content of those soils. β-diversity values, the number of measured and estimated dominant OTUs, and their distribution among the three sites showed that microbial communities from the two natural forests were much more similar to each other than they were to communities from the poplar plantation, suggesting an effect of the forest conversion on the composition and diversity of soil microbial communities. α-diversity in cultivated forest soils had narrower temporal fluctuations than in natural forest soils, suggesting higher temporal stability of microbial communities. Overall, we demonstrated that the conversion from natural forest to forest plantation altered soil microbial communities, changing their structure, lowering their diversity, and causing a spatial and temporal homogenization.